Delineating the Boundaries Between Nonmonogamy and Infidelity: Bringing Consent Back Into Definitions of Consensual Nonmonogamy With Latent Profile Analysis. Issue 4 (3rd May 2020) - Hangen, Forrest; Crasta, Dev; Rogge, Ronald D.
Abstract : To gain insight into the mixed findings surrounding Consensual Nonmonogamy (CNM), this study developed the Triple-C model of commitment, conceptualizing relationship structures with three key dimensions: mutual consent, communication, and comfort. Latent profile analyses in an online sample (N = 1, 658) identified five classes of relationship structures: two monogamous groups (68%; representing earlier- and later-stage relationships), CNM relationships (7.7%, marked by low interest in monogamy and high levels of mutual consent, comfort, and communication around commitment and EDSA), partially-open relationships (13%, with more mixed attitudes toward monogamy and lower consent, comfort, and communication), and one-sided EDSA relationships (11%, in which one partner desires monogamy while the other partner engages in EDSA with low levels of mutual consent, comfort, and communication). The monogamous and CNM groups demonstrated high levels of relationship and individual functioning, whereas the partially-open and one-sided nonmonogamous groups demonstrated lower functioning. These findings highlight the diversity of nonmonogamy that likely exists within self-report classifications like "swingers" and "open relationships, " providing a possible explanation for the mixed findings in previous work. Decision tree analyses identified a 4-item algorithm (COMMIT4) that classifies individuals into these groups with 93% accuracy, offering a tool for incorporating relationship structure diversity in future work.